Post-transplant diabetes mellitus: risk factors and outcomes in a 5-year follow-up - Rossi, Matheus Rizzato; Mazzali, Marilda; de Sousa, Marcos Vinicius (Frontiers in Clinical Diabetes and Healthcare, 2024)
Introduction: Kidney transplantation is associated with an increased risk of posttransplant diabetes mellitus (PTDM), impacting recipient and graft survivals. The incidence of PTDM ranges from 15% to 30%, with most cases occurring in the first year post-transplant. Some clinical and laboratory characteristics pre- and post-transplant may be associated with a higher PTDM incidence in a more extended follow-up period. This study aimed to analyze the prevalence of PTDM among renal transplant recipients without previous DM diagnosis during a five-year post-transplant follow-up, as well as clinical and laboratory characteristics associated with a higher incidence of PTDM during this period. Material and methods: Single-center retrospective cohort including kidney transplant recipients older than 18 years with a functioning graft over six months of follow-up between January and December 2018. Exclusion criteria were recipients younger than 18 years at kidney transplantation, previous diabetes mellitus diagnosis, and death with a functioning graft or graft failure within six months post-transplant. Results: From 117 kidney transplants performed during the period, 71 (60.7%) fulfilled the inclusion criteria, 18 (25.3%) had PTDM diagnosis, and most (n=16, 88.9%) during the 1st year post-transplant. The need for insulin therapy during the hospital stay was significantly higher in the PTDM group (n=11, 61.1% vs. n=14, 26.4%, PTDM vs. non-PTDM). Other PTDM risk factors, such as older age, donor’s and recipient’s age, high body mass index, HLA mismatches, and cytomegalovirus or hepatitis C virus infections, were not associated with PTDM occurrence in this series. During 5-year post-transplant follow-up, the graft function remained stable in both groups. Conclusions: The accumulated incidence of PTDM in this series was similar to the reported in other studies. The perioperative hyperglycemia with the need for treatment with insulin before hospital discharge was associated with PTDM.